Time Spent With Children and Working Parents’ Willingness to Medicate ADHD-Like Behaviors - Bora Pajo (SAGE Open, 2013)
How much time parents spend with their children is likely to influence their judgments of children’s behaviors and the behaviors themselves. In the diagnosis of children with attention-deficit/hyperactivity disorder (ADHD), parents are key informants and decide whether their children should receive medication. This exploratory study investigates the relationship between working parents’ willingness to medicate ADHD-like behaviors and the time they can spend with their children during a regular workday. The participants (409 parents of 5- to 17- year-old children reporting having no child with emotional or behavioral problems and 87 reporting having such a child) were drawn from a population-based telephone survey of parents stratified by race and ethnicity in two urban Florida counties. Path analysis models, controlling for selected sociodemographic and household variables, showed that spending more time with one’s children during a regular workday and self-identifying as African American were negatively related to willingness to medicate among parents of children with problems. Among parents reporting no children with problems, only the number of children in the household and the parent-type household showed relationships to willingness to medicate, while mothers were more likely than fathers to spend more time with children. These observed relationships were of moderate effect but underscore the importance to initiate studies using valid measures of quantity and quality of parental time spent with ADHD children, and to query parents on these points when assessing the information they provide to clinicians.